Bringing constructed languages back to the debate: The contributions of interlinguistics to general linguistics - Fians, Guilherme (Investigationes Linguisticae, 2022)
In the first half of the twentieth century, the fields of interlinguistics and Esperanto studies emerged as branches of linguistics focused on the study of languages designed for international communication (such as Volapük, Esperanto, and Ido). Yet, why are there specific fields to study language creation and why should linguists care about this? Looking at the history of constructed languages, this article explores the institutionalization of interlinguistics by focusing on the history of the Centre for Research and Documentation on World Language Problems (CED, in its Esperanto acronym), a research center founded in 1952 whose developments encapsulate certain aspects of this broader narrative. From an analysis of CED’s 44th Esperanto Studies Conference, in 2022, I flesh out the potential of interlinguistics to contribute back to linguistics and to the humanities disciplines that originated it. Ultimately, this article calls for the reinsertion of constructed languages into general linguistics debates.